2020
DOI: 10.1590/1518-8345.3382.3350
|View full text |Cite
|
Sign up to set email alerts
|

Protective and risk factors for women’s mental health after a spontaneous abortion

Abstract: Objective: to examine personal and contextual protective and risk factors associated with women’s mental health after a spontaneous abortion. Method: a cross-sectional study was carried out where 231 women who had experienced spontaneous abortions in the past 4 years answered a self-reporting online questionnaire to assess their mental health (symptoms of depression, anxiety, perinatal grief) and to collect personal as well as contextual characteristics. Results: women who had experienced spontaneous abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 41 publications
1
32
3
1
Order By: Relevance
“… The study indicated that depressive symptoms and perinatal grief may persist long after a miscarriage, for more than 2 years after the loss Results also revealed that symptoms of perinatal grief decreased significantly over time only for women with children and for women who were satisfied with health services. Fair DeMontigny et al, 2020 https://doi.org/10.1590/1518-8345.3382.3350 Canada Protective and risk factors for women’s mental health after a spontaneous abortion. 231 women who had experienced spontaneous abortion in the past 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The study indicated that depressive symptoms and perinatal grief may persist long after a miscarriage, for more than 2 years after the loss Results also revealed that symptoms of perinatal grief decreased significantly over time only for women with children and for women who were satisfied with health services. Fair DeMontigny et al, 2020 https://doi.org/10.1590/1518-8345.3382.3350 Canada Protective and risk factors for women’s mental health after a spontaneous abortion. 231 women who had experienced spontaneous abortion in the past 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 1 , it is possible to note that, among the selected studies, 34.78% were published by researchers from North America (the USA and Canada) (Clark et al, 2021 ; DeMontigny et al, 2017 , 2020 ; Goldstein et al, 2019 ; Hawthorne et al, 2016 ; Keim et al, 2017 ; Kerns et al, 2018 ; Paris et al, 2016 ), being 4.34% originated in Latin America, resulting from a partnership between Brazil and Canada (Paris et al, 2016 ). The other articles include Europe (UK, Spain, Sweden, and France), corresponding to 30.43% of the publications selected (Druguet et al, 2018 ; Kokou-Kpolou et al, 2018 ; Lafarge et al, 2017 , 2020 ; Ridaura et al, 2017 ; Volgsten, et al, 2018a , b ; Volgsten, et al, 2018a , b ), Asia (India, Jordan, Sri Lanka, Israel), with 17.39% of the publications selected (Al-Maharma et al, 2016 ; Kulathilaka et al, 2016 ; Roberts & Lee, 2014 ; Roberts et al, 2021 ), and Australia (13.04%) (Inati et al, 2018 ; Pollock et al, 2021 ; Wilson et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study on quality of life among women with and without recurrent miscarriage using the 36-Item Short Form Survey (SF-36) and the Hospital Anxiety and Depression Scale (HADS) demonstrated that women with recurrent miscarriage reported extensive functional disability, and lower level of well-being compared to women without recurrent miscarriage (5). Results from another study indicated that anxiety, depression, and perinatal grief can persist for a long period after miscarriage (6). Also, more attention should be given to women in vulnerable situations, such as immigrant women, women with low socioeconomic status, or childless women.…”
Section: Introductionmentioning
confidence: 99%
“…Also, more attention should be given to women in vulnerable situations, such as immigrant women, women with low socioeconomic status, or childless women. Beyond those personal and contextual factors, the quality of the conjugal relationship and the level of satisfaction with health care appeared to be important protective factors against mental health problems after a spontaneous abortion (6). In couples with recurrent pregnancy loss (RPL), medical professionals need to take a holistic and couple-focused approach in their treatment including attention to the psychological impact and cumulative effect of the multiple RPL on the couple (7).…”
Section: Introductionmentioning
confidence: 99%